Islamic Religious Development Model to Develop Students' Character at MAN 1 Mojokerto - Seprina, Seprina; Rahmat, Rahmat (Anjasmoro: Islamic Interdisciplinary Journal, 2024)
The Religious Development Model is very important to apply in madrasas to be able to develop the character of students by trying to educate, guide, practice, develop, and supervise students to form good personal character following Islamic teachings. Implementing a model of religious formation, it will greatly influence the formation of students' character, which requires special guidance to avoid character deviations. This research aims to analyze the implementation of the Islamic religious formation model at MAN 1 Mojokerto and to analyze the implications of the Islamic religious formation model for developing the character of students at MAN 1 Mojokerto. By using qualitative research and a case study approach. Data collection techniques use interviews, observation, and documentation. The data sources are informants who are directly involved in implementing religious activities, namely the head of the madrasah, the Religious Development Coordinator, Teachers, and Students. Results from this research: First, the implementation of the religious formation model at MAN 1 Mojokerto uses a structural and mechanical model with the religious formation activities implemented namely carrying out congregational prayers, Tahlil, Istighosah, and Shalawatan, joint prayer, Tahfid Al-Qur'an, evening recitations, and activities to commemorate Islamic holidays. Apart from being carried out through the learning process in the subjects of Aqidah Akhlak, Fiqh, Skiing, and Al-Qur'an Hadith, religious formation is also carried out through extracurricular activities such as tahfidz, banjari, and remas (mosque youth). Second, the implications of the Islamic religious formation model for developing the character of students at MAN 1 Mojokerto include: a) The structural model has implications for strong Islamic character and exemplary educators with the emergence of religious character values, discipline and responsibility. b) The mechanical model has implications for developing attitudes of obedience and discipline, forming ethics and morals, strengthening social skills, forming a leadership spirit, and forming spiritual independence with the emergence of religious character values, honesty, discipline, hard work, tolerance, social care, friendship, feeling. curious, democratic, responsible, and independent in worship.